Siklus Hidup Organisasi : Suatu Analisis Perkembangan Organisasi - Sam'un Jaja Raharja (Business Administration Department - Universitas Katolik Parahyangan, 2010)
Organization is born from the idea or proposal which is declare by the founder. Intheir way, every organization will experience up and down, stagnant, or even collapse,if planning wasn’t implemented and systematic effort. Organization life cycle givesa description and analysis about phase of the organization’s development, conditioncharacteristics which were encounter in the every development and also implicationswhich were faced in every development phase, also treatment needed to turn backorganization objective.Keywords: organization life cycle, organization development